Penerapan Manajemen Sumber Daya Manusia dengan Pendekatan “Multidimensional” dalam Meningkatkan Pembangunan Desa Bonder - Mashuri, johan (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2018)
This study aims to determine the application of human resource management with a multidimensional approach in improving development in Bonder Village. The multidimensional approaches include (1) political approach, (2) legal approach, (3) sociocultural approach, (4) administrative approach, (5) economic approach and (6) technological approach. The type of research used is qualitative research. multidimensional in improving rural development. This qualitative research seeks to prioritize the ability of researcher analysis on the basis of facts found with a combination of existing theoretical concepts. The study was located in Bonder Village, West Praya District, Central Lombok Regency. From a political standpoint, some of the Bonder villagers are actively involved in better village development. While from the legal approach, some of the Bonder villagers are legally aware of the importance of the balance between their rights and obligations. From the sociocultural approach, the people of Bonder Village still emphasize socio-cultural rules or norms that apply in their area and are actualized in village development activities. Furthermore, from the administrative approach, residents of Bonder Village community in determining an ordinary goal to cooperate or form a small organization that is informal, while economic approaches and technological approaches are still lacking so there is need for counseling, education and empowerment of village government officials.